Can Traditional Straight-leg Swaddling Influence Developmental Dysplasia of the Femoral Trochlea? An In Vivo Study in Rats. Issue 9 (29th September 2022) - Wang, Shengjie; Ji, Gang; Li, Weifeng; Tang, Shiyu; Dong, Zhenyue; Xu, Chenyue; Chen, Xiaobo; Zhao, Chao; Wang, Fei
Abstract: Background: It has been reported that trochlear dysplasia occurs very early in development, and environmental factors like swaddling may cause developmental dysplasia of the hip, which is associated with a shallower trochlear groove. However, to our knowledge, there are no definitive studies about the relationship between trochlear dysplasia and traditional straight-leg swaddling. Questions/purposes: Using a rat model of femoral trochlear dysplasia, we asked: Does straight-leg swaddling for 1 and 2 weeks in newborn Wistar rats alter the femoral trochlea with respect to (1) gross morphology, (2) histologic appearance, as well as (3) trochlear sulcus angle, width, and depth? Methods: Eighty-four newborn Wistar rats (44 females and 40 males) were divided into two equal groups: 42 in the unswaddled group and 42 in the swaddled group; each group was comprised of 22 females and 20 males. In the swaddled group, the rats were wrapped in surgical tape to maintain hip and knee extension to simulate traditional human straight-leg swaddling. To determine whether longer periods of swaddling were associated with more severe trochlear dysplasia, 21 rats in each group were euthanized at 1 and 2 weeks, respectively, and the gross morphology of the femoral trochlea was observed by one observer blinded to condition. Then hematoxylin and eosin staining of the femoral trochlea was performed and the distribution and number of the chondrocytes of the trochlear groove were viewed through a microscope. The trochlear sulcus angles, depth, and width were measured by an experienced technician blinded to condition. Results: By observing the gross morphology, we found that the trochlear groove in the swaddled group became qualitatively flatter compared with the unswaddled group at 1 week, and at 2 weeks, the trochlear groove became much shallower. At 1 and 2 weeks, histologic examinations showed obvious qualitative changes in the distribution and number of chondrocytes of the trochlear groove in the swaddled than in the unswaddled groups. In the swaddled group, trochlear dysplasia was more common at 2 weeks, occurring in 62% (26 of 42 [16 of 22 females and 10 of 22 males]) versus 33% (14 of 42 [8 of 22 females and 6 of 20 males]) at 1 week. At 1 week, the swaddled group showed more trochlear dysplasia compared with the unswaddled group as measured by angle of the trochlear groove (137° ± 6° versus 132°± 3.6°, mean difference 5° [95% confidence interval 2.9° to 7.2°]; p < 0.001), depth of the trochlear grove (0.28 ± 0.04 mm versus 0.31 ± 0.02 mm, mean difference 0.03 mm [95% CI 0.01 to 0.04]; p < 0.001). At 2 weeks, the swaddled group showed more severe trochlear dysplasia than at 1 week compared with the unswaddled group as measured by the angle of the trochlear groove (135° ± 6.0° versus 128° ± 4.8°, mean difference 7° [95% CI 5.7° to 10.4°]; p < 0.001), depth of the trochlear grove (0.32 ± 0.04 mm versus 0.36 ± 0.02 mm, mean difference 0.04 mm [95% CI 0.03 to 0.06]; p < 0.001). There was no difference in the width of the trochlear sulcus between the swaddled and the unswaddled groups at 1 week (1.29 ± 0.14 mm versus 1.30 ± 0.12 mm, mean difference 0.01 mm [95% CI -0.05 to 0.07]; p = 0.73) and 2 weeks (1.55 ± 0.12 mm versus 1.56 ± 0.12 mm, mean difference 0.01 mm [95% CI -0.05 to 0.07]; p = 0.70). Conclusion: Our results indicate that traditional straight-leg swaddling could induce trochlear dysplasia in this model of newborn rats. With an increased swaddling time of 2 weeks, more severe trochlear dysplasia appeared in the swaddled group. Clinical Relevance: Our findings suggest that traditional straight-leg swaddling may impair trochlear development in the human neonate and lead to trochlear dysplasia in infants. We believe our animal model will be useful in future work to observe and study the change of cartilage and subchondral bone in each stage of the development of trochlear dysplasia and the change of mechanotransduction-associated proteins (such as, TRPV4/ Piezo1 and CollagenⅡ) in cartilage and subchondral osteocytes. It will also be helpful to further investigate the mechanism of developmental femoral trochlea dysplasia caused by biomechanical changes.